Detection of recombinant growth hormone by evanescent cascaded waveguide coupler on silica‐on‐silicon. Issue 5 (24th July 2012) - Ozhikandathil, Jayan; Packirisamy, Muthukumaran
Abstract An evanescent wave based biosensor is developed on the silica‐on‐silicon (SOS) with a cascaded waveguide coupler for the detection of recombinant growth hormone. So far, U ‐bends and tapered waveguides are demonstrated for increasing the penetration depth and enhancing sensitivity of the evanescent wave sensor. In this work, a monolithically integrated sensor platform containing a cascaded waveguide coupler with optical power splitters and combiners designed with S ‐bends and tapper waveguides is demonstrated for an enhanced detection of recombinant growth hormone. In the cascaded waveguide coupler, a large surface area to bind the antibody with increased penetration depth of evanescent wave to excite the tagged‐rbST is obtained by splitting the waveguide into multiple paths using Y splitters designed with s ‐bends and subsequently combining them back to a single waveguide through tapered waveguide and combiners. Hence a highly sensitive fluoroimmunoassay sensor is realized. Using the 2D FDTD (Finite‐difference time‐domain method) simulation of waveguide with a point source in Rsoft FullWAVE, the fluorescence coupling efficiency of straight and bend section of waveguide is analyzed. The sensor is demonstrated for the detection of fluorescently‐tagged recombinant growth hormone with the detection limit as low as 25 ng/ml. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)